Diamonds in nature a guide to rough diamonds - Tappert, Ralf (Springer, 2011)
Diamonds in Nature: A Guide to Rough Diamonds illustrates and explains the unique properties of natural diamonds, such as their crystal shapes, colors, surface textures, and mineral inclusions. It also contains up-to-date information about the origin and scientific significance of diamonds. With more than 200 high-quality photographs and drawings, it is an invaluable reference for the professional geoscientist and anyone with an interest in diamonds.